Computational design of a novel anti-inflammatory drug - Louvoulina, Maria; Ekonomopoulou, Vasia; Papageorgiou, Maria (Open Schools Journal for Open Science, 2021)
Computer-aided drug design is among the most valuable tools we have in order to design new drug molecules. Herein, with the aid of the Drug Design Workshop platform, we describe our efforts to propose a new anti-inflammatory drug with a high selectivity upon the COX-2 target protein.